Effectiveness Test of Petai Seed Methanol Extract Against Cholesterol of Wistar Strain Rats Induced by High Fat Feed - Yustini Alioes (Faculty of Medicine, Universitas Andalas, 2023)
Objective: This study aims to determine the effectiveness of the methanol extract of petai seeds on the cholesterol levels of Wistar strain rats induced by a high-fat diet. Methods: True experimental research with post test only control group design using 25 rats which were divided into 5 groups, namely the control group (negative and positive) and the treatment group (treatments 1, 2 and 3). High-fat diet for 30 days was given to groups K+, P1, P2, and P3. Then continued with the administration of methanol extract of petai seeds in the treatment group with each dose of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW for 10 days. The mean cholesterol levels were checked using the CHOD-PAP method and data were analyzed using the Kruskal-Wallis and Post-Hoc Mann-Whitney nonparametric tests. Results: The results showed that the administration of petai seed methanol extract at doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW had a significant difference with the positive control group (p<0.05). Conclusion : This study showed the methanol extract of petai seeds had effectiveness in lowering cholesterol levels in wistar strain rats induced by high fat diet.